Smartphone hearing screening with integrated quality control and data management. (December 2014) - Swanepoel, De Wet; Myburgh, Hermanus C.; Howe, David M.; Mahomed, Faheema; Eikelboom, Robert H.
Abstract Objective: To determine if a smartphone application could be used as a calibrated screening audiometer with real-time noise monitoring for school screening using automated test sequences. Design: The investigation comprised three studies. Study 1 evaluated calibration accuracy across four Samsung S5301 smartphones (Android v4.0.4) using commercial Sennheiser HD202 headphones. Study 2 involved referencing smartphone microphone sensitivity to narrowband noise intensity as measured in octave bands by a sound-level meter between 30 and 75 dB SPL (5 dB increments). Study 3 compared screening outcomes of smartphone based and conventional hearing screening. Study sample: Study 2: 15 normal-hearing subjects (age range, 18–22 years; all female). Study 3: 162 children (324 ears) aged 5 to 7 years. Results: Smartphone calibration at 20, 30, and 40 dB was within 1 dB of recommended reference equivalent thresholds levels. Microphone calibration for noise monitoring had maximum variability across phones of 0.9, 0.6, and 2.9 dB at 1, 2, and 4 kHz, respectively, from reference intensities (30 to 75 dB SPL). Screening outcomes demonstrated no significant difference between smartphone and conventional audiometry with an overall referral rate of 4.3% and 3.7%, respectively. Conclusions: The newly developed smartphone application can be accurately calibrated for audiometry with valid real-time noise monitoring, and clinical results are comparable to conventional screening.